2009
DOI: 10.1242/jeb.025387
|View full text |Cite
|
Sign up to set email alerts
|

Diving into old age: muscular senescence in a large-bodied, long-lived mammal, the Weddell seal (Leptonychotes weddellii)

Abstract: SUMMARYClassic aging theory postulates the absence of pronounced organismal senescence in wild animals since mortality probably occurs first. Large-bodied, long-lived mammals are a recognized exception to this tenet, yet organismal senescence has not been investigated to date in such mammals in the wild. Furthermore, oxidative stress theory of aging supports the suggestion that exercise hypoxia, as regularly incurred during apneustic foraging in diving mammals might lead to cellular dysfunction and accelerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 50 publications
7
69
0
1
Order By: Relevance
“…As muscle Mb loads often correlate with dive durations (Noren and Williams 2000;Lestyk et al 2009), higher Mb concentrations in deep-diving Weddell seals make their O 2 -storage capacities more similar to those previously reported in other phocid species capable of extended breath hold diving Lestyk et al 2009;Hassrick et al 2010). That Weddell seals expend energy to continue producing equivalent RBCs and iron-containing O 2 -carrying proteins during all times of the year (i.e., reduced and intense foraging periods, and the energetically expensive molt period), and also through senescence (Hindle et al 2009 demonstrates the importance of maintaining aerobic diving capacities. One possibility is that any summer diving activity and exercise would be sufficient to maintain protein production in Weddell seals.…”
Section: Discussionsupporting
confidence: 70%
“…As muscle Mb loads often correlate with dive durations (Noren and Williams 2000;Lestyk et al 2009), higher Mb concentrations in deep-diving Weddell seals make their O 2 -storage capacities more similar to those previously reported in other phocid species capable of extended breath hold diving Lestyk et al 2009;Hassrick et al 2010). That Weddell seals expend energy to continue producing equivalent RBCs and iron-containing O 2 -carrying proteins during all times of the year (i.e., reduced and intense foraging periods, and the energetically expensive molt period), and also through senescence (Hindle et al 2009 demonstrates the importance of maintaining aerobic diving capacities. One possibility is that any summer diving activity and exercise would be sufficient to maintain protein production in Weddell seals.…”
Section: Discussionsupporting
confidence: 70%
“…Penguins primarily use the pectoral muscles for propulsion (see Bannasch, 1995;Alexander, 1992); thus, theoretically muscle development could influence swimming capacity (Hindle et al, 2009). Muscle efficiency is obviously a difficult parameter to estimate in free-ranging animals, and this hypothesis cannot be verified.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that in both longand short-lived wild mammal species, muscular deficits and a reduction in fitness can precede reproductive senescence (e.g. Abrams, 1991;Hindle et al, 2009a;Hindle et al, 2009b). This decrease in fitness may be due in part to early age-related changes, which likely negatively impact individual survivorship in the wild, as the risk of predation increases and foraging capabilities are reduced.…”
Section: A M Horner D W Russ and A R Bikneviciusmentioning
confidence: 99%